Effects of strict vehicle restrictions on various travel modes: A case study of Zhengzhou, China. (October 2022) - Lin, Shichao; Zhu, Songwei; Li, Xiangmin; Li, Ruimin
Highlights: Vehicle restriction improves public transport ridership and ride-hailing demand. Short-term and long-term effects on various travel modes are discussed. Traffic conditions are much better, although vehicle reduction is less than expected. Multisource mass data of various travel modes are utilized. Abstract: Vehicle restriction policies are introduced worldwide to alleviate traffic congestion and promote public transportation trips. Many cities in China have been taking the one-day- per -week (ODPW) restriction policy as a regular traffic management measure, while in special cases, the stricter odd-and-even (OAE) vehicle restriction policy is implemented for contingency. However, empirical evidence on the impact of these restrictions on various transportation modes in cities remains lacking. By using multisource mass data of various travel modes in Zhengzhou, China, this study investigates the practical effects of strict vehicle restriction policies from two perspectives of resident trip characteristics, namely, travel demand of various travel modes (subways, buses, and ride-hailing services) and road network traffic conditions. Results highlight a significant increase in the travel demand of alternative travel modes as the policy shifted from ODPW to OAE, with ride-hailing orders enduring a greater impact than public transportation. The long-term impact of these policies on these travel modes, except for buses, tends to be moderate. While traffic conditions have significantly improved as a result of these policies, their effects on reducing the number of vehicles on the road are less than expected. This study contributes to a comprehensive interpretation of the effects of strict vehicle restrictions and provides insights for making rational policy decisions.